Land-Use and Cover Changes (1988–2002) around Budongo Forest Reserve, NW Uganda: Implications for Forest and Woodland Sustainability - Mwavu, E. N.; Witkowski, E. T. F. (Land degradation & development, 2008)
Land-use and cover changes around Budongo Forest Reserve (BFR) were analysed from multi-temporal LandSat images (1988 and 2002) and associated field-based studies in 2003–2004. Three major land-use and cover classes: forest/woodland, sugarcane plantations and grassland/shifting-cultivation/settlements were clearly discriminated. The area under sugarcane cultivation increased over 17-fold, from 690 ha in 1988 to 12729 ha in 2002, with a concomitant loss of about 4680 ha (8 2 per cent) of forest/woodland, mainly on the southern boundary of BFR. Land-use and cover changes were a result of (a) agricultural expansion, (b) increasing human population, exacerbated by large influxes of refugees, (c) conflicts of interest and political interference in the management of BFR and (d) unclear land tenure. Agriculture is the main land-use practice and source of income to local people, with commercial sugarcane and tobacco as the primary cash crops. Individual smallholder sugarcane plantations covered distances ranging from 30 to 1440m along the BFR edge, with no buffer zone, resulting in direct conflicts between farmers and forest wild animals. There is an ever-increasing need for more land for agricultural expansion, resulting in continued loss of forest/woodland on private/communal lands and encroachment into BFR. This unsustainable agricultural expansion and the local people’s perception of BFR as an obstacle to agriculture, threatens the conservation of its threatened wild plants (e.g. Raphia farinifera) and the endangered chimpanzees. Therefore, their sustainable management for both development and conservation will require strong and incorruptible institutions that will seek a balance between resource exploitation and conservation.
Keywords: Agricultural practices; Change-detection; Forest/woodland loss; Forest management; Land-tenure